Urban Farming Practices and Constraints to Urban Agriculture in Bauchi Metropolis (Journal of Innovative Research, 2025)
The rise in urban population, accompanied by growing poverty and hunger, has triggered the need to engage in urban agriculture in order to address the challenges of food insecurity in urban centers. This research is aimed at assessing the practices and constraints to urban agriculture in Bauchi metropolis with a view to improving urban food security. Primary and secondary data were used for the study. A total of 285 copies of the structured questionnaire were administered to urban farmers in the eight political wards within the Bauchi metropolis using a chain referral sampling technique. Secondary data were obtained from the review of relevant literature. Data collected were analysed using Statistical Package for Social Science (SPSS) involving descriptive and inferential methods. Respondent Agreement Index (RAI) was used to measure the constraints to urban agriculture in the study area. Findings revealed that majority of farmers who practice UA do not own lands. For this reason, they eventually borrow or rent lands for UA. Farmers engage in urban farming for extra sources of food and to complement their source of income. The major constraints to urban agriculture are lack of tenure security, limited land area and poor access to microcredit facilities. The study recommended that space allocation for urban agriculture should be integrated into the master plan of Bauchi metropolis.